The dribbling agility test as a potential tool for evaluating the dribbling skill in young soccer players - Bekris, E.; Gissis, I.; Kounalakis, S. (Research in Sports Medicine, 2018)
The present study examined the construct validity and reliability of a new dribbling agility test (DAT) that incorporates reactive agility and multiple change of direction. To check its` validity, (a) DAT was performed by four groups (under 10, under 12, under 14 and under 16 yrs) of young soccer players (n = 125 in each group) and (b) a regression analysis was conducted to define the best DAT predictors. The reliability of DAT was assessed with repeated measurements. This test can differentiate the dribbling skill between groups (p < 0.01). Furthermore, 68% of the observed variance in DAT was explained by zigzag dribbling test, Illinois agility test, reaction time and running speed. The test-retest reliability was high in all groups (ICC = 0.77 - 0.90, p < 0.01). It was concluded that DAT can be a potential tool to evaluate the dribbling performance in young soccer players.